Achieving the MDGs in Yemen : An Assessment - Al-Batuly, Abdulmajeed; Al-Hawri, Mohamed; Cicowiez, Martin; Lofgren, Hans; Pournik, Mohammad (World Bank, Washington, DC, 2014)
Once the current political crisis in Yemen has been resolved, it will be ever more urgent to speed up progress, including Millennium Development Goal (MDG) achievements. Drawing on simulations with the Maquette for MDG Simulations (MAMS), a model for strategy analysis, and a linked microsimulation model, this paper addresses Yemen's MDG challenges. A first simulation set considers scaled-up government actions with the aim of fully achieving the 2015 international MDG targets with required additional financing from foreign or domestic sources. The main finding is sobering but not surprising: given the required expansion of MDG -- related services, on-time achievement of key MDG targets does not appear to have been a realistic objective even if the government, hypothetically, would have expanded services with grant aid financing starting from 2005; macroeconomic stability, government efficiency, and the production of tradables would all have suffered due to the size of spending and aid increases as well as the resulting real exchange rate appreciation. The results suggest that countries, instead of relying on international targets, should set MDG targets grounded in their own reality. In light of these results, the authors designed a second simulation set that is focused on the remaining period up to 2015, and on what may be feasible once the current conflict has been settled. The simulations introduce moderate increases in foreign aid or government allocative efficiency. The government uses the resulting fiscal space for spending and service expansion in infrastructure and human development without losses in productive efficiency. The results suggest that, under these conditions, substantial improvements could still be achieved.